2020
DOI: 10.1097/pas.0000000000001558
|View full text |Cite
|
Sign up to set email alerts
|

High-grade Neuroendocrine Carcinomas of the Vulva

Abstract: Vulvar high-grade neuroendocrine carcinomas (HGNECs) are rare and primarily thought to represent Merkel cell carcinoma (MCC). We present the clinicopathologic features of 16 such cases, the largest series to date. Patients were most often White, postmenopausal, and symptomatic from a palpable vulvar mass/nodule. Tumors ranged from 0.7 to 6 cm and most commonly involved the labium majus. Majority of the cases were pure HGNECs (15/16) with small cell (SC) morphology (14/16); 2 were large cell neuroendocrine carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Regardless of their potential differences in etiology and risk factors, neuroendocrine neoplasms of the vulva share similar morphologic appearance and clinical behavior with neuroendocrine neoplasms from other sites of the gynecological tract. In their recent study, Chen et al reported that high-risk human papilloma virus was positive in all SCNEC and negative in all Merkel cell carcinomas [35]. On the other hand, recent studies regarding Merkel cell carcinoma revealed an extremely strong association with infection by a polyoma virus, termed Merkel cell polyomavirus [36,37].…”
Section: Neuroendocrine Neoplasms Of the Vulvamentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of their potential differences in etiology and risk factors, neuroendocrine neoplasms of the vulva share similar morphologic appearance and clinical behavior with neuroendocrine neoplasms from other sites of the gynecological tract. In their recent study, Chen et al reported that high-risk human papilloma virus was positive in all SCNEC and negative in all Merkel cell carcinomas [35]. On the other hand, recent studies regarding Merkel cell carcinoma revealed an extremely strong association with infection by a polyoma virus, termed Merkel cell polyomavirus [36,37].…”
Section: Neuroendocrine Neoplasms Of the Vulvamentioning
confidence: 99%
“…Small cell carcinoma, as well as large cell carcinoma of the vulva should also be surgically excised, and undergo adjuvant therapy. There are no clear protocols for these cases, but patients can receive either adjuvant chemotherapy with or without radiation therapy and some could even benefit from adjuvant immunotherapy [35].…”
Section: Neuroendocrine Neoplasms Of the Vulvamentioning
confidence: 99%
“…High-grade neuroendocrine carcinomas (HGNECs) of the vulva are extremely rare, but when they occur, they usually present as aggressive neoplasms [ 1 ]. These tumors can be further classified into Merkel cell carcinoma, small cell neuroendocrine carcinoma (SCNEC), and large cell neuroendocrine carcinoma according to morphological, immunohistochemical, and virological characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…These tumors can be further classified into Merkel cell carcinoma, small cell neuroendocrine carcinoma (SCNEC), and large cell neuroendocrine carcinoma according to morphological, immunohistochemical, and virological characteristics. Previously, most of the vulvar HGNECs were considered to be Merkel cell carcinomas [ 1 ]. However, Chen et al [ 1 ] performed detailed immunohistochemical and virological analyses of 12 HGNECs with pure small cell morphology and reported that out of those 12 cases, 6 (50%) were SCNECs and 6 (50%) were Merkel cell carcinomas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation